Productivity Improvement in Pathology Laboratories Using Motion and Time Study Techniques - Canan CINAR; Afsun Ezel ESATOGLU (Federation of Turkish Pathology Societies, 2024)
Objective: This study aimed to determine the standard time required for the performed job and to examine the standard job critically for productivity improvement in the pathology laboratory. Material and Methods: In this study that was conducted at a tertiary teaching hospital, observation, fishbone diagram, and flow charts were used to collect the information about the job process. All employees were observed from September 2017 to June 2018. The observations were recorded by video camera in order to overcome the Hawthorne effect. Nine basic procedure steps were followed for productivity improvement. Results: Within the scope of the study, the jobs of `trimming tissue blocks` and `sectioning of tissue blocks` was selected. The standard time required was 0.19 minutes for `trimming tissue blocks` and 0.34 minutes for `sectioning of tissue blocks`. The procedure steps, named `Removal of tissue block` and `Fixing the block to the device`, were removed from the flow chart to define the improved method. The implementation of the improved method brought in a gain of 11.28 work days per year. Conclusion: It is obvious that the pathology laboratory needs to take certain measures to improve working conditions and increase efficiency. Our results demonstrate applying the study techniques could reduce the workload and processing time. This study also shows that the study techniques can be applied in the hospital laboratory. Incorporation of all pathology technicians in the change or innovation process will be important in maintaining the achievements.